2021
DOI: 10.3390/su13126679
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Game Design Elements Used in Digital Game-Based Language Learning

Abstract: Considerable changes have occurred in language learning with the introduction of gameful approaches in the classroom and the increase in the popularity of language applications like Duolingo. A review of existing studies on such approaches to language learning shows that gamification tends to be the most popular approach. However, this popularity has been achieved at the expense of other gameful approaches, such as the use of digital games. To gain a clearer picture of the developments and gaps in the digital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 119 publications
0
17
1
Order By: Relevance
“…It facilitates the incorporation of project sustainability thinking and management as an integral and harmonised part of project management teaching. In game-based learning, students can experience situations that are most relevant to learn the topic [68].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…It facilitates the incorporation of project sustainability thinking and management as an integral and harmonised part of project management teaching. In game-based learning, students can experience situations that are most relevant to learn the topic [68].…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Furthermore, games can provide challenging experiences that demand players to be continuously committed while providing appropriate feedback to create a sense of competition [54,55]. For example, a recent review suggested that digital games can be used effectively as gameful approaches to language learning [56]. There is also evidence that commercial off-the-shelf action video games (but not other types of games) can improve reading efficiency, even if they do not include any direct orthographic or phonological stimulation [57][58][59].…”
Section: Developmental Dyslexiamentioning
confidence: 99%
“…This can be done through games, applications or other systems that create a challenge for the users (Hansch, 2015). Exposure to digital games and their surrounding environment has been shown to improve target language acquisition to the point where gamers, on average, have more target language vocabulary than non-gamers (Govender & Arnedo-Moreno, 2021).…”
Section: B Gamification and Edutainmentmentioning
confidence: 99%